Association of skin autofluorescence with plaque vulnerability evaluated by optical coherence tomography in patients with cardiovascular disease. (July 2018) - Fujino, Yusuke; Attizzani, Guilherme F.; Tahara, Satoko; Wang, Wei; Takagi, Kensuke; Naganuma, Toru; Yabushita, Hiroto; Tanaka, Kentaro; Sato, Tomohiko; Watanabe, Yusuke; Mitomo, Satoru; Kurita, Naoyuki; et al.
Abstract: Background and aims: Accumulation of advanced glycation end products (AGEs) can be measured non-invasively by skin autofluorescence (SAF) whose values are elevated in patients with cardiovascular disease (CVD). Optical coherence tomography (OCT) is an intravascular imaging modality that could allow visualization of plaque composition. We aim to examine the relationship between SAF and plaque composition evaluated by frequency-domain OCT in patients with CVD. Methods: We prospectively enrolled 108 patients with CVD, who underwent OCT images during percutaneous coronary intervention (PCI). We divided the population into two groups: high SAF group (greater than or equal to 2.6) and low SAF one (less than 2.6). OCT findings were then compared between high and low SAF groups. Results: The high SAF group showed much more thin cap fibroatheroma (TCFA), and calcified or ruptured plaques compared to the low SAF group. In multivariable analysis, low-density lipoprotein-cholesterol (LDL) (odds ratio: 1.15; 95% confidence interval: 1.00 to 1.32; p  = 0.043), TG (OR for 10 mg/dl increase: 1.04; 95% confidence interval: 1.01 to 1.13; p  = 0.016), and SAF (4.28; 1.86 to 9.84; p < 0.001) were independent correlates of TCFA, whereas SAF (2.61; 1.02 to 6.70; p  = 0.047), estimated glomerular filtration rate (0.68; 0.49 to 0.93; p  = 0.017) and LDL (1.19; 1.01 to 1.41; p  = 0.037) were independent predictors of ruptured plaques. SAF and diabetes were independently associated with calcified plaques. Conclusions: High SAF were associated with plaque vulnerability in patients with CVD, thus suggesting the clinical utility of SAF measurement in identifying high-risk patients for future cardiovascular events. Highlights: The present study provides OCT insights on coronary artery plaque vulnerability in patients with different levels of SAF. SAF levels independently predicted plaque instability in patients with CVD, such as thin cap fibroatheroma (TCFA), plaque rupture, and calcification. SAF may be a novel biomarker that helps identify high-risk patients for future cardiovascular events and death.